2007
DOI: 10.1016/j.resuscitation.2007.01.032
|View full text |Cite
|
Sign up to set email alerts
|

The cardioprotective effect of dexmedetomidine on global ischaemia in isolated rat hearts

Abstract: Dexmedetomidine exhibited a cardioprotective effect on global ischaemia in the isolated rat heart model, which was mediated by alpha-2 adrenergic stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 34 publications
4
79
0
6
Order By: Relevance
“…Regarding the heart, Okada et al described that Dex protected the myocardium against global IR. They discuss that vasoconstriction elicited by Dex may be triggering ischemic preconditioning [17]. Furthermore, our previous studies have shown that Dex activated the RISK pathway in the myocardium [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the heart, Okada et al described that Dex protected the myocardium against global IR. They discuss that vasoconstriction elicited by Dex may be triggering ischemic preconditioning [17]. Furthermore, our previous studies have shown that Dex activated the RISK pathway in the myocardium [15].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the pharmacological mechanism involved in Dex-dependent cardioprotection [15,16]. Given the biphasic vascular effects of vasoconstriction and vasodilatation of the drug at coronary vessels, it was first proposed that Dex could mimic the effect of ischemic preconditioning [17].…”
Section: Introductionmentioning
confidence: 99%
“…A more likely explanation for the cardioprotective effect of DEX is that the drug alters the myocardial oxygen balance (74,75). The decrease in emergence-associated myocardial ischemic load caused by DEX may be explained by its sympatholytic effects, which improve the myocardial oxygen supply/demand ratio.…”
Section: Myocardial I/rmentioning
confidence: 99%
“…Dexmedetomidine has been shown to have organ protective effects in animal models particularly in modulation of cytokine and inflammatory mediators in variety of ischaemia and ischemic-reperfusion injury in animal [78][79][80][81][82][83]. However, such protective effects are not evident in human studies.…”
Section: Dexmedetomidine and Organ Protectionmentioning
confidence: 99%
“…One study has demonstrated that use of dexmedetomidine in post-bypass period in coronary bypass surgery had lower incidence of acute kidney injury [84]. Few other animal experimental study has shown organ protective effects of dexmedetomidine on myocardial protection [82,85] neuronal protection in spinal cord injury [86][87][88][89], reduction in cerebral vasospasm after sub-arachnoid haemorrhage, [89] prevention of retinal apoptosis in retinal ischaemia [90], preventive effects in Acute lung injury [91], visceral and renal protection in ischemic-repurfusion injury [81][82][83][84]92,93]. The ability to protect against organ dysfunction, notably myocardial, renal and neuronal, may yet to be the defining characteristic of this class of drug in human being.…”
Section: Dexmedetomidine and Organ Protectionmentioning
confidence: 99%